An optimized microfluidic paper‐based NiOOH/Zn alkaline battery. Issue 3 (3rd July 2018) - Burrola, Samantha; Gonzalez‐Guerrero, Maria Jose; Avoundjian, Ani; Gomez, Frank A.
Abstract: In this paper, an alkaline nickel oxide hydroxide/zinc (NiOOH/Zn) battery featuring a cellulose matrix separator between electrodes is presented. The metallic electrodes and the paper separator are inserted in a layer‐by‐layer assembly that provides mechanical stability to the system resulting in a lightweight and easy‐to‐use device. The battery was optimized for the amount of NiOOH‐ink used at the cathode (11.1 mg/cm 2 ) and thickness of the paper membrane separating the electrodes (360 μm). The battery was able to function using a small volume (75 μL) of 1.5 M potassium hydroxide (KOH) producing a maximum voltage, current density, and power density of 1.35 ± 0.05 V, 10.62 ± 0.57 mA/cm², and 0.56 ± 0.01 mW/cm², respectively. The system displayed a maximum current of 23.9 mA and a maximum power of 1.26 mW. Moreover, four batteries connected in series were able to power a small flameless candle for approximately 22 min. This work has potential in fulfilling the demands for short‐term and lightweight power supplies.